Investigation on mechanism of Hexavalent chromium bioreduction by Escherichia sp. TH-1 and the stability of reduction products. Issue 3 (June 2022) - Wang, Xitong; Li, Hao; Huang, Huayan; Luo, Huanyan; Luo, Shihua; Jiang, Lili; Feng, Su; Xu, Heng
Abstract: Hexavalent chromium (Cr(VI)) was proved to be a carcinogen to organisms and threaten health of human beings through food chains. In order to detect a more economical and efficient method to remove Cr(VI) from contaminated sites, a Cr(VI) reducing strain named TH-1 was isolated from aerobic activated sludge and identified as Escherichia sp. by 16 S rDNA sequence analysis. The Cr(VI) removing performance of TH-1 was elucidated under different environmental conditions (temperature, pH, initial Cr (VI) concentration and metal ions) to detect the optimum condition, and the potential mechanisms of Cr(VI) reduction were explained including micro-characterization and stability test of reduction product. As the result, while inhibited by Cd 2+ existence, TH-1 could grow and remove Cr(VI) in a wide range of temperature and pH (optimum at 37 ℃ and pH7.0), with the process being promoted by Cu 2+, Ni 2+ and Fe 3+ . The results of X-ray Diffraction, X-ray photoelectron spectroscopy confirmed that the reduced Cr(VI) product was mainly organic-Cr (III) complex, and Fourier Transform infrared spectroscopy showed that functional groups such as –OH, -COOH and CO etc. were Cr binding sites. Afterwards, the stability of the organic-Cr (III) complex reduced by strain TH-1 were much more stable than Cr (III) chemically reduced by FeS, the stability of which decreased significantly from pH 9 to pH 14, but rarely changed under near-neutral and acidic condition. Hence, TH-1 had great prospects for reducing Cr (VI) under different environmental conditions with long-term effect, which was significant for the remediation of Cr (VI) influenced environmental sites. Graphical Abstract: ga1 Highlights: A strain with high chromium tolerance ability and Cr (VI) reduction ability was isolated. The potential mechanism of Cr (VI) bio-reduction by the strain was analyzed. Comparing the stability of Cr (VI) by bio-reduction and chemical reduction. The stability of bio-reduced Cr (Ⅲ) at different pH was evaluated.